Perkiraan Tinggi Badan Berdasarkan Panjang Kaki pada Etnis Batak Karo Tahun 2024 - Julanda, Baari Putra; Petrus, Asan; Lubis, Adriansyah (Publikasi Indonesia, 2025)
Body height is a basic unit for assessing growth and nutrition, but measuring body height can be hindered by muscle weakness, joint problems, or spinal deformities. Estimating a person's height is an important parameter in forensic examinations. An alternative method for measuring a person's height in forensic cases, as well as when human body parts are found at mass disaster sites, is to calculate height according to identification perspectives. Furthermore, estimating stature from skeletal fragments is also of great interest in forensic science. Anthropometry is a systematic measurement method that expresses human body and skeletal dimensions quantitatively. Anthropometry is often viewed as a traditional tool and may be a basic tool in biological anthropology. This is due to the increasing number of disaster events causing mass deaths that require victim identification from fragmented human remains. Footprint analysis helps in estimating an individual's stature because of the strong positive correlation between stature and foot size; footprints are also considered indicators of a person's skeletal and body structure. Method: This research is an analytical study with a cross-sectional design aimed at examining the relationship between foot length and body height in the North Sumatran community, aged 21-25 years, of Batak Karo ethnicity. Results: Foot length and body height in males and females have a significant relationship with a p-value < 0.05 (P = 0.001), with a very strong correlation level; r > 0.8 (0.800-1.000). Foot length has a strong correlation with body height, making foot length a good predictor of body height.